A CONTEXTUAL PHYSICS LEARNING MODEL ON PROJECTILE MOTION THROUGH HOMBO BATU ACTIVITY WITHIN THE LOCAL WISDOM OF SOUTH NIAS - Harefa, Darmawan (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This study aims to develop a contextual learning model for the topic of projectile motion by integrating Hombo Batu activities as a form of local wisdom from the South Nias community. Hombo Batu, or the traditional stone-jumping ritual, is a physical activity rich in two-dimensional kinematics elements, such as initial velocity, angle of elevation, and parabolic trajectory. The research employed the Research and Development (R&D) method based on Sugiyono's development model, which includes the following stages: identifying potential and problems, data collection, product design, validation, revision, and limited trials. Validation results from subject matter experts and media experts indicated that the developed learning model achieved a high level of validity (Aiken’s V > 0.85), categorized as “highly feasible.” A limited trial conducted with junior high school students in South Nias showed that the model effectively improved students' understanding of projectile motion, with an average N-Gain score of 0.56 (moderate to high category). Additionally, the implementation of the model led to increased learning motivation and greater appreciation of local culture among the students. This model not only enhances conceptual understanding in physics but also strengthens students’ character and cultural identity through a learning approach that is contextual, meaningful, and applicable. Therefore, the Hombo Batu-based contextual learning model is recommended as an innovative alternative for teaching physics, particularly in regions rich in local cultural values.